Gamification and virtual reality in occupational safety teaching - Silva, Rayssa V. da; Simões, Francisco P. M.; V. Valério, Bianca M. (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais Estendidos do XXVII Simpósio de Realidade Virtual e AumentadaDO - 10.5753/svr_estendido.2025.15388, 2025)
This study presents a serious game in virtual reality for occupational safety education in construction. Developed in Unreal Engine 5.5® with Meta Quest 2®, it allows free navigation, hazard identification through menus, and real-time feedback in realistic scenarios such as scaffolding, excavations, and sanitary facilities. Preliminary results confirm system functionality, immersive interaction, and potential to replicate inspection practices. Next steps include implementing scoring and assessing educational impact.